Evaluasi Kebijakan Operasi Daerah Selesaikan Kemiskinan (ODSK) Di Provinsi Sulawesi Utara - delano pinasang (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2022)
This study takes the title "Evaluation of Regional Operational Policies to Resolve Poverty (ODSK) in North Sulawesi Province." This research is a description of the current evaluation of policies for accelerating poverty reduction in North Sulawesi Province, including mainly in terms of regulations, institutions, and human resources. in the ODSK Policy. The purpose of this study was to find out and analyze how Regional Operational Policies to Solve Poverty in North Sulawesi, with challenges and obstacles in the process, especially for Regulation, ODSK Institutional Position, and Evaluation of Human Resources. The research method used by the author is an exploratory method with data analysis through an inductive approach. The way to collect data is by means of interviews and documentation. Based on the results of the analysis by the author, it turns out that the Regional Operations Policy to Solve Poverty in North Sulawesi still has a lot to improve and is not as optimal as expected, in terms of regulations that need and can be upgraded to regional regulations, then the optimal form of coordination team structure is in accordance with Permendagri No. . 53 of 2020, as well as the use of Human Resources that can still be improved all of which to achieve appropriate and accurate results.Furthermore, in the future, it is hoped that this ODSK program and policy can continue to a better level, if it gets a stronger and binding legal umbrella, so that the implementation of ODSK can be more integrated, and synergize at the District and City levels throughout North Sulawesi Province, as well as A more efficient team after adjusting to the existing regulations, for the sake of the acceleration of good poverty reduction throughout the North Sulawesi region.